2023
DOI: 10.1108/jpbm-06-2022-4020
|View full text |Cite
|
Sign up to set email alerts
|

Does crowdsourcing necessarily lead to brand engagement? The role of crowdsourcing cues and relationship norms on customer-brand relationships

Abstract: Purpose This paper aims to examine how the relationship norms established between customers and brands influence customer perceptions of crowdsourcing (vs firm-generated) cues. Design/methodology/approach Four studies (N = 851) examine the moderating role of relationship norms on product labeling cues (crowdsourcing vs firm-generated) effects on brand engagement, and the underlying mechanism of self-brand connection. Findings The findings suggest that crowdsourcing (vs firm-generated) cues lead to higher b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 104 publications
1
12
0
Order By: Relevance
“…Second, brand prominence helps attract backers with strong brand loyalty and sense of connection to the brand. Stronger consumer engagement is seen for recognizable brands across studies on crowdsourced product innovation (Herter et al, 2023) and cocreation (Chen et al, 2022;Nawaz et al, 2023). Similarly, prior research has shown that potential backers are more likely to support campaigns when they are familiar with the featured brand (Fortezza et al, 2023).…”
Section: Hypothesesmentioning
confidence: 89%
See 2 more Smart Citations
“…Second, brand prominence helps attract backers with strong brand loyalty and sense of connection to the brand. Stronger consumer engagement is seen for recognizable brands across studies on crowdsourced product innovation (Herter et al, 2023) and cocreation (Chen et al, 2022;Nawaz et al, 2023). Similarly, prior research has shown that potential backers are more likely to support campaigns when they are familiar with the featured brand (Fortezza et al, 2023).…”
Section: Hypothesesmentioning
confidence: 89%
“…Building on the literature on brand prominence (Han et al, 2010;Sääksjärvi et al, 2015;Tellis et al, 2019), this study illustrates how conspicuous displays of visual and textual brand elements pertaining to compatible brands can exert spillover effects on third-party entities, such as aftermarket offerings. Second, while there is some branding research in the literature on crowd-based initiatives, such as crowdsourced product innovation (Herter et al, 2023) and cocreation (Chen et al, 2022;Nawaz et al, 2023), branding perspectives are noticeably absent in the context of crowdfunding (Moradi and Badrinarayanan, 2021). Given the increasing popularity of crowdfunding as a financing mechanism for new ventures (Moradi et al, 2023), this study not only delineates the differential effects of brand elements on crowdfunding success but also sheds light on how such elements can complement the effects of other campaign elements.…”
Section: Theoretical Implicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Brand love is an example of a high emotional, high functional relationship (Bairrada et al, 2018). The distinction between exchange relationships, in which benefits are provided to get something in return, versus communal relationships, characterized by prioritizing the relationship partner's needs, seems to align logically with this combination of dimensions (Aggarwal, 2004(Aggarwal, , 2009Herter et al, 2023). The combination of the strength and valence dimensions has also been used to classify brand relationship concepts: brand like, brand satisfaction (weak, positive); brand love, brand passion (strong, positive); brand dislike, brand avoidance (weak, negative); brand hate, brand divorce (strong, negative); and brand indifference (no strength) (Fetscherin et al, 2019;Fetscherin and Heinrich, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past research examines backers’ motives for engaging in crowdfunding but pays far less attention to the behavioral manifestations of engagement (Efrat et al , 2019; Shneor et al , 2021). Recent research on crowdsourcing (Herter et al , 2023) suggests that, in general, crowdfunding could lead to higher brand engagement, yet the opposite effect remains unexplored. To address this gap, this research examines how SMBE may impact BCF participation, ultimately enhancing brand loyalty – recently defined as “a relationship stakeholder(s) develop with a brand that is exhibited by repurchasing, engaging, promoting/advocating, and/or cocreating/co-owning the brand” (Parris and Guzmán, 2023, p. 218).…”
Section: Introductionmentioning
confidence: 99%